2010
DOI: 10.1002/mrm.22393
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of MRI data encoded with arbitrarily shaped, curvilinear, nonbijective magnetic fields

Abstract: A basic framework for image reconstruction from spatial encoding by curvilinear, nonbijective magnetic encoding fields in combination with multiple receivers is presented. The theory was developed in the context of the recently introduced parallel imaging technique using localized gradients (PatLoc) approach. In this new imaging modality, the linear gradient fields are generalized to arbitrarily shaped, nonbijective spatial encoding magnetic fields, which lead to ambiguous encoding. Ambiguities are resolved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
150
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 71 publications
(155 citation statements)
references
References 23 publications
4
150
0
Order By: Relevance
“…Physiological limitations in the switching rate of such fields have led to the development of alternative geometries for creating linear encoding fields (1), with the aim of reducing the maximal dB/dt by making the gradient fields more local. The general concept of PatLoc (Parallel Imaging Technique using Localized Gradients) (2,3) is to relax the requirement that the spatial encoding magnetic fields (SEMs) must vary linearly across the field-of-view (FoV) by introducing SEMs exhibiting spatial variation of higher order than standard linear gradients. Parallel imaging technology enables MR imaging with spatially ambiguous encoding fields and, once understood, this additional degree of spatial encoding freedom may lead to improved gradient performance or reduced peripheral nerve stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological limitations in the switching rate of such fields have led to the development of alternative geometries for creating linear encoding fields (1), with the aim of reducing the maximal dB/dt by making the gradient fields more local. The general concept of PatLoc (Parallel Imaging Technique using Localized Gradients) (2,3) is to relax the requirement that the spatial encoding magnetic fields (SEMs) must vary linearly across the field-of-view (FoV) by introducing SEMs exhibiting spatial variation of higher order than standard linear gradients. Parallel imaging technology enables MR imaging with spatially ambiguous encoding fields and, once understood, this additional degree of spatial encoding freedom may lead to improved gradient performance or reduced peripheral nerve stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…To enable both positive and negative maxima the discussed optimization function can be adapted by introducing an absolute value operation inside the sum. This enables optimization of SEMs for enhanced local orthogonality more freely without neglecting oscillating SEMs which could be used for PatLoc imaging [8,10] that is not bound to spherical harmonics. Allowing for this degree of freedom, Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies enforced approximate linearity over a reduced volume for monoplanar gradients to accommodate the unavoidable field decay or were specifically designed for small target volumes [4][5][6][7]. In our recent studies [8][9][10] we have shown that reasonable spatial encoding can be achieved as long as the local gradients of the encoding fields are non-collinear and have a non-zero magnitude. With the field geometries proposed it becomes possible to image a large field of view (FOV), comparable with that produced by built-in linear whole-body gradient systems.…”
mentioning
confidence: 84%
See 2 more Smart Citations